KESEJAHTERAAN BURUH HARIAN LEPAS (BHL) PERKEBUNAN KELAPA SAWIT (STUDI KASUS PT.ANUGERAH NIAGA SAWINDO DI KECAMATAN ROKAN IV KOTO DAN PT.MASUBA CITRA MANDIRI DI KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU PROVINSI RIAU) - Refa Novella Refa Novella; Paus Iskarni (JURNAL BUANA, 2023)
ABSTRACTThis study aims to determine the income of casual daily workers, to find outthe need for food, clothing and shelter, to find out the fulfillment of the healthand education needs of the children of casual daily workers and to find out wherecasual daily workers live at PT. Anugerah Niaga Sawindo and PT. Masuba CitraMandiri. This research uses a descriptive method . The results of the study showthat, the income of freelance daily workers at PT. Anugerah Niaga Sawindo ishigher than PT. Masuba Citra Mandiri. Meeting the needs of food, clothing andboards in both companies have been met properly. Fulfilling the health needs oftemporary daily workers at these two companies can be said to be prosperousbecause if a family member is sick they can take them to a health facility fortreatment. Meanwhile, to meet the educational needs of the children of casualworkers, PT. Masuba Citra Mandiri is more prosperous than PT. SawindoCommercial Award. The distribution of temporary workers' residences uses aclustering pattern around PT. Anugerah Niaga Sawindo and PT. Masuba CitraMandiri.Keywords : Well-Being, Freelance, Palm Oil Palantation